Paleogeographic approach for the oil and gas potential assessment of the Khadum Formation (Lower Oligocene) in Pre-Caucasus basin - A. N. Stafeev; A. V. Stoupakova; E. A. Krasnova; A. A. Suslova; R. S. Sautkin; Ya. A. Shitova; M. L. Makhnutina; M. E. Voronin (Georesursy, 2024)
Authors used the paleogeographic approach to identify the different facies generation potential, mark out the areas with the highest organic matter and its types, analyse the reservoir quality for oil and gas potential assessment of the Pre-Caucasus basin Khadum formation. The greatest prospects in the Western and Central parts of the basin characterized by terrestrial and partly mixed organic matter types and are associated with the facies of the Sarpinsk-Armavir channel where discharge currents from the Volga-Don basin occurred. The same organic matter types can be related to clastic fans drawn from the north. In the Eastern part the main prospects are associated with unconventional black shale reservoirs with the predominantly aquatic organic matter, isolated on the top and base by the thick series of seal rock.